DANA INFAK SEBAGAI PONDASI KEUANGAN MASJID NAMIRA LAMONGAN - Hengky Asmarakandi; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
The background of this research is the existence of zero infak phenomenon in Namira Lamongan mosque. This phenomenon encourages researchers to take research that discusses the financial management strategies used until the manager is brave in applying zero infak system. This research uses qualitative approach with case study strategy. Data collection is done through interviewing techniques with related parties and the documents concerned. Analytical techniques carried out in this research are the technique of source triangulation, pattern matching techniques, and descriptive qualitative analysis techniques. The results of this study indicate that the financial management strategy relies on the founders who are usually referred to as yayasan. The phenomenon of zero infak Namira mosque occurs because the mosque's expenditure is too large compared infak income. So the yayasan fund becomes the main role in covering all the shortcomings.Keywords: infak, financial management, mosque finance, Namira Lamongan MosqueREFFERENCESAl-Faruq, A. (2010). Panduan Lengkap Mengelola dan Memakmurkan Masjid. Solo: Pustaka Arafah.Al-Fauzan, A. (2008). Fiqih Seputar Masjid. Jakarta: Pustaka Imam Asy-Syafi’i.Ayub, M. (1996). Manajemen Masjid. Jakarta: Gema Insani.Daft, Richard L. (2002). Manajemen Edisi Kelima Jilid I. Jakarta: ErlanggaDewan Masjid Indonesia. (2003). Buku Panduan Praktis Manajemen Pengelolaan Masjid Edisi Pertama. Surabaya: PW DMI Jawa TimurGazalba, S. (1975). Masjid Pusat Ibadat dan Kebudayaan Islam.Jakarta : Pustaka Antara.Kasmir. 2010. Pengantar Manajemen Keuangan. Jakarta: Kencana Prenada Media GroupKurniawan, S. ( 2014). Masjid dalam Lintasan Sejarah Umat Islam. Jurnal Khatulistiwa, Vol. IV/ No.2/ September 2014Munawir, S. 2007. Analisis Laporan Keuangan. EdisiKedua. Yogyakarta : Liberty.Muslim, A. (2004). Manajemen Pengelolaan Masjid. Jurnal Aplikasi Ilmu-ilmu Agama Vol. V/ No. 2/ Desember 2004Musthofa, T. (2010). Upaya Menghidupkan Kembali Risalah Masjid Seperti Zaman Rasulullah. Jurnal Ulama, (online), Tahun III/ Vol.III/ No.1/ April2010, (http://isjd.pdii.lipi.go.id, diakses 10 Desember 2017)Putra, M. Vithro H.( 2014). Preferensi Takmir Masjid dalam Memilih Layanan Perbankan di Surabaya (A Qualitative Multiple Case Study di Delapan Masjid). Surabaya: Universitas AirlanggaRiyanto, B. (2001). Dasar-Dasar Pembelanjaan Perusahaan. Yogyakarta: BPFE YogyakartaShiu, YM. 2004. Determinants of United Kingdom General Insurance Company Performance. British Actuarial Journal, vol. 10, pp. 1079 – 1110,Sochimin (2015). Praktik Manajemen Keuangan Masjid. Purwokerto: IAIN Purwokerto